Sunda Pangolin Manis javanica (Mammalia: Pholidota: Manidae) of Gaya Island, Sabah - Jephte Sompud; Cynthia Boon Sompud; Pei, Kurtis Jai-Chyi; Sun, Nick Ching-Min; Rimi Repin; Fred Tuh (Jott Note, 2019)
The Sunda Pangolin Manis javanica is naturally present in Gaya Island, Sabah, but its population status is largely unknown. Results from a recent survey using camera traps indicated the presence of a few individuals, who were strictly nocturnal. There is a strong indication that the population in Gaya Island is in danger of local extinction. There is also an urgent need to conduct an in-depth study to gather scientific information for further conservation action.